Wide-field strain imaging with preferentially aligned nitrogen-vacancy centers in polycrystalline diamond. (19th December 2016) - Trusheim, Matthew E; Englund, Dirk
Abstract: We report on wide-field optically detected magnetic resonance imaging of nitrogen-vacancy centers (NVs) in type IIa polycrystalline diamond. These studies reveal a heterogeneous crystalline environment that produces a varied density of NV centers, including preferential orientation within some individual crystal grains, but preserves long spin coherence times. Using the native NVs as nanoscale sensors, we introduce a three-dimensional strain imaging technique with high sensitivity ( < 10 − 5 Hz –1/2 ) and diffraction-limited resolution across a wide field of view.